An updated review of epidemiological characteristics, immune escape, and therapeutic advances of SARS-CoV-2 Omicron XBB.1.5 and other mutants - Liu, Zongming; Li, Jiaxuan; Pei, Shanshan; Lu, Ying; Li, Chaonan; Zhu, Jiajie; Chen, Ruyi; Wang, Di; Sun, Jingbo; Chen, Keda (Frontiers in Cellular and Infection Microbiology, 2023)
The rapid evolution of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has led to the emergence of new variants with different genetic profiles, with important implications for public health. The continued emergence of new variants with unique genetic features and potential changes in biological properties poses significant challenges to public health strategies, vaccine development, and therapeutic interventions. Omicron variants have attracted particular attention due to their rapid spread and numerous mutations in key viral proteins. This review aims to provide an updated and comprehensive assessment of the epidemiological characteristics, immune escape potential, and therapeutic advances of the SARS-CoV-2 Omicron XBB.1.5 variant, as well as other variants.